2006
DOI: 10.1016/j.mseb.2006.02.054
|View full text |Cite
|
Sign up to set email alerts
|

Basic materials research programs at the U.S. Air Force Office of Scientific Research

Abstract: The Air Force Office of Scientific Research (AFOSR) annually sponsors approximately 5000 research scientists at 1000 universities and laboratories, generating about 10,000 Ph.D. graduates per decade, all expected to publish their basic research findings in peer-reviewed journals. After a brief introduction of the nature of AFOSR's support to basic research in the U.S. and international scientific communities, work it supports at the frontiers of materials science is highlighted. One focused research theme that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…7 Smart materials are expected to contribute greatly to the safety and durability of polymeric components without high costs of active monitoring or external repair. [2][3][4][5] Homo-and copolymers of furfuryl methacrylate (FMA) are interesting materials because of the presence of reactive furfuryl functionality. [8][9][10][11] This reactive diene functionality can be used for the Diels-Alder (DA) reaction using a suitable bismaleimide (BM) as dienophile.…”
Section: Introductionmentioning
confidence: 99%
“…7 Smart materials are expected to contribute greatly to the safety and durability of polymeric components without high costs of active monitoring or external repair. [2][3][4][5] Homo-and copolymers of furfuryl methacrylate (FMA) are interesting materials because of the presence of reactive furfuryl functionality. [8][9][10][11] This reactive diene functionality can be used for the Diels-Alder (DA) reaction using a suitable bismaleimide (BM) as dienophile.…”
Section: Introductionmentioning
confidence: 99%
“…Microcracks are the precursors to structural failure [126] and the ability to heal them will enable structures with longer lifetimes and less maintenance. Consequently, significant research interest and growing investment from scientific funding agencies is being shown [127][128][129]. Though the potential benefits are quite high, there are several practical limitations (such as crack healing kinetics and stability of the healing functionality to environmental conditions) that need to be overcome in order for the benefits to be realized in society.…”
Section: Future Directions and Conclusionmentioning
confidence: 99%
“…in compliant polymeric resins represent a large class of manmade lightweight structural materials that have been finding rapidly expanding applications in aerospace, aeronautical and ground vehicles, sports utilities, gas and liquid pipeline transportation, offshore and marine construction, and civil infrastructure, among others [1][2][3][4][5][6][7][8][9][10][11]. Such broad applications are resulting mainly from the unique properties of PMCs including their high specific stiffness and strength, excellent fatigue tolerance and immunity to corrosion, amicable manufacturability, etc., [1][2][3]5]. As microstructures, PMCs are highly heterogeneous materials, and when subjected to external loading, high stress inhomogeneities and stress singularities exist in PMCs, which result in their progressive damage [12].…”
Section: Introductionmentioning
confidence: 99%